1974
DOI: 10.1029/ja079i016p02269
|View full text |Cite
|
Sign up to set email alerts
|

High-energy cosmic ray intensity increase of nonsolar origin and the unusual Forbush decrease of August 1972

Abstract: A series of spectacular cosmic ray events, which included two relativistic solar particle enhancements and three major Forbush decreases, was registered by ground-based cosmic ray monitors beginning on August 4, 1972. Among these, the Forbush decrease that occurred on August 4-5 exhibited extremely interesting and complex behavior, the prominent features of which are a preincrease (PI-1) prior to the largest Forbush decrease (FD-2) during the recovery of which an abrupt universal time increase (PI-2) occurred.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1976
1976
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The magnetic field configuration of the accompanying shock [Lockwood et al, 1975] led to an intensity decrease in MTs deep underground [Swinson, 1973] and in IC and underground MTs at Yakutsk [Filippov et al, 1973] as well as the multidirectional MTs at Nagoya [Sekido et al, 1973]. Agrawal et al [1974] report on FD recorded by a global network of NMs and surface MTs (see their Figure 4). Medrano et al [1975] discuss a model for the associated ICME.…”
Section: Forbush Decrease Of August 1972mentioning
confidence: 99%
“…The magnetic field configuration of the accompanying shock [Lockwood et al, 1975] led to an intensity decrease in MTs deep underground [Swinson, 1973] and in IC and underground MTs at Yakutsk [Filippov et al, 1973] as well as the multidirectional MTs at Nagoya [Sekido et al, 1973]. Agrawal et al [1974] report on FD recorded by a global network of NMs and surface MTs (see their Figure 4). Medrano et al [1975] discuss a model for the associated ICME.…”
Section: Forbush Decrease Of August 1972mentioning
confidence: 99%
“…Vernov et al (1970a, b) during other events observed low energy particles accumulated behind shocks. For this 5 August event Agrawal et al (1974) give a similar explanation and for this particular event such a possibility was tested by Otaola et al (1977a) and Perez-Enriquez (private communication). When the field is perturbed, the particle mean free path is very small and so particles are convected by the solar wind, i.e.…”
Section: The Cosmic Ray Increase 3--7 Utmentioning
confidence: 96%
“…It reaches the minimum of the F.d. at 1 or 2 UT, of 5 August, depending not only on the asymptotic direction of the station (Agrawal et al, 1974) but also on the rigidity of the particles. Note that all stations with cutoff rigidities Pc < 1.4 GV which observed the GLE, i.e.…”
Section: The Large Fdmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of investigators have reported the short-term characteristics of the daily variation, where they have selected continually occurring days of high and low amplitudes of diurnal variation (Tiwari, 1994;Agrawal et al, 1974, Tiwari, 1995. These results have pointed out significant departures in the time of maximum as well as their association with higher harmonics.…”
Section: Introductionmentioning
confidence: 99%